Review of S&T policy plans in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Louk Box et. al. (2003) Review of Science and Technology plans in ACP countries, University of Maastricht, Maastricht.